Identification of Quorum-Sensing Inhibitors Disrupting Signaling between Rgg and Short Hydrophobic Peptides in Streptococci - Chaitanya Aggarwal (American Society for Microbiology, 2015)
ABSTRACT Bacteria coordinate a variety of social behaviors, important for both environmental and pathogenic bacteria, through a process of intercellular chemical signaling known as quorum sensing (QS). As microbial resistance to antibiotics grows more common, a critical need has emerged to develop novel anti-infective therapies, such as an ability to attenuate bacterial pathogens by means of QS interference. Rgg quorum-sensing pathways, widespread in the phylum Firmicutes, employ cytoplasmic pheromone receptors (Rgg transcription factors) that directly bind and elicit gene expression responses to imported peptide signals. In the human-restricted pathogen Streptococcus pyogenes, the Rgg2/Rgg3 regulatory circuit controls biofilm development in response to the short hydrophobic peptides SHP2 and SHP3. Using Rgg-SHP as a model receptor-ligand target, we sought to identify chemical compounds that could specifically inhibit Rgg quorum-sensing circuits. Individual compounds from a diverse library of known drugs and drug-like molecules were screened for their ability to disrupt complexes of Rgg and FITC (fluorescein isothiocyanate)-conjugated SHP using a fluorescence polarization (FP) assay. The best hits were found to bind Rgg3 in vitro with submicromolar affinities, to specifically abolish transcription of Rgg2/3-controlled genes, and to prevent biofilm development in S. pyogenes without affecting bacterial growth. Furthermore, the top hit, cyclosporine A, as well as its nonimmunosuppressive analog, valspodar, inhibited Rgg-SHP pathways in multiple species of Streptococcus. The Rgg-FITC-peptide-based screen provides a platform to identify inhibitors specific for each Rgg type. Discovery of Rgg inhibitors constitutes a step toward the goal of manipulating bacterial behavior for purposes of improving health. IMPORTANCE The global emergence of antibiotic-resistant bacterial infections necessitates discovery not only of new antimicrobials but also of novel drug targets. Since antibiotics restrict microbial growth, strong selective pressures to develop resistance emerge quickly in bacteria. A new strategy to fight microbial infections has been proposed, namely, development of therapies that decrease pathogenicity of invading organisms while not directly inhibiting their growth, thus decreasing selective pressure to establish resistance. One possible means to this goal is to interfere with chemical communication networks used by bacteria to coordinate group behaviors, which can include the synchronized expression of genes that lead to disease. In this study, we identified chemical compounds that disrupt communication pathways regulated by Rgg proteins in species of Streptococcus. Treatment of cultures of S. pyogenes with the inhibitors diminished the development of biofilms, demonstrating an ability to control bacterial behavior with chemicals that do not inhibit growth.